ORGANIZATIONAL AND ECONOMIC ASPECTS OF WASTE MANAGEMENT IN RUSSIA - Oksana Momotova; Eugene Sabel'nikov; Irina Savchenko (Вестник Северо-Кавказского федерального университета, 2022)
In the article the theoretical generalization of domestic and foreign experience of waste management and regional experience of the Stavropol region, identified key discussion issues and trends in the development of legislation in the field of waste management. In particular, it studies the stages of development of the waste management system abroad, including the role of waste as a potential energy source. As well as the level of development of these trends in Russia. Designated organizational-economic and legal adjustments in the regulatory process for the treatment of waste by a new Federal law. Discusses the shortcomings andfragmented nature of certain provisions of Federal laws, as well as the possible directions of development of the mechanism of regulation of waste management in the Russian Federation. Summarizes the experience of the Stavropol region as a pilot region to create an integrated system of waste management. Formulated the main thesis - the need of transition to an integrated waste management system, involving the maintenance of economic and administrative mechanisms to encourage waste reduction, separation and recycling.